STRATEGIC MANAGEMENT TOOLS FOR ACTIVATING INNOVATION ACTIVITIES OF EXPORT-ORIENTED ENTERPRISES - Bordaiev, Vladislav (Social Development: Economic and Legal Issues, 2025)
The article explores the ways of strategic management as a tool for activating the inventive activity of export-focused businesses in the circumstances of global competition. The relevance of the research is due to the necessity of export-oriented enterprises to boost their innovative capacity to ensure competitiveness in international markets amid constant changes in the external environment and integration into global economic processes. The goal is to develop and support effective strategic management tools for activating the innovative activity of export-focused firms in order to increase their competitiveness in international markets. The study is aimed at discovering effective strategic tools and management methods that can stimulate the inventive activity of export-oriented businesses and ensure their sustainable development in a global competitive environment. The study utilized methods including analysis and synthesis of scientific literature, comparative analysis of strategic instruments, expert evaluations, alongside modeling and a systematic approach to develop advice on how to trigger the innovative activity of export-focused businesses. The results demonstrated that implementing a comprehensive set of strategic instruments markedly boosts the innovative activity of export-oriented enterprises and aids their competitiveness in global markets, while removing critical obstacles to innovative development. The core is a systematic approach to implementing strategic instruments that considers the specifics of export-oriented enterprises and allows adapting innovative solutions to the conditions of the external market and the company’s internal assets. The article describes the core and development of strategic management within the framework of globalization. The theoretical bases of strategic management and its role in ensuring the competitiveness of businesses in global markets are explored. The ideas of innovation management are examined, especially regarding export-focused businesses. The strategic methods employed by businesses in foreign economic operations are reviewed. The specifics of export-oriented businesses and their innovative work in the present economic conditions are explained. Strategic tools for stimulating the innovative activity of export-oriented enterprises are organized. A matrix model of integration of strategic blocks and tools for innovative expansion of export-oriented businesses is offered. The results suggest that the effective utilization of strategic management tools is a vital factor in enabling the inventive endeavors of export-driven companies and ensuring their competitiveness and long-term viability in worldwide markets. Further research should focus on refining strategic management methodologies, taking into account digitalization, progress in artificial intelligence, and novel forms of international collaboration to enhance the innovative potential of export-oriented companies.